Lysine Requirement of Fast Growing Chickens — Effects of Age, Sex, Level of Protein Deposition and Dietary Lysine Efficiency - Samadi; Frank Liebert (The Journal of Poultry Science, 2007)
N-balance studies were carried out to assess the lysine requirement of fast growing chickens (Cobb 500) at different sex and age depending on crude protein deposition and efficiency of dietary lysine utilisation. The experiments were conducted within three age periods (I : 10-25d ; II : 30-45d ; III : 50-65d) and 72 chickens (36 males, 36 females) per age period. Experimental diets with six levels of graded CP content were based on high protein (HP)-soybean meal, wheat gluten and crystalline amino acids (L-Thr, DL-Met, L-Arg) in order to create lysine (4.30g Lys/100gCP) as the first limiting dietary amino acid (constant ratio Lys : Met+Cys : Thr : Arg=1 : 1.01 : 0.91 : 1.14). For application of a nonlinear N-utilization model, nitrogen maintenance requirement (NMR) and theoretical maximum for daily nitrogen retention (NRmaxT) were established as model parameters for further assessment of the lysine requirement depending on age, sex and daily CP-deposition. As an example, the calculated lysine requirement concentration for 60% of the theoretical potential for daily CP-deposition (10-25d : 1.10% lysine, 60g daily feed intake ; 30-45d : 1.03% lysine, 140g daily feed intake ; 50-65d : 0.96% lysine, 170g daily feed intake) was in close agreement with published data. However, the predicted feed intake is one of the most important factors of influence when amino acid requirement concentrations are established. The level of daily CP-deposition and the dietary amino acid efficiency as important factors influencing the amino acid requirement data need more attention in future requirement studies.